CEO Compensation from M&As in Australia - Bugeja, M.; da Silva Rosa, R.; Duong, Lien; Izan, H. (Wiley-Blackwell Publishing Ltd., 2012)
We investigate Australian CEO compensation following mergers and acquisitions (M&As). We find CEOs of acquiring firms receive higher compensation in the year of M&A completion and one year after. We also find a positive correlation between CEO compensation and firm performance, and some measures of CEO effort and skill in completing the deal. However, CEOs of bidding firms receive a lower bonus and other compensation if they wield more managerial power (that is, if the CEO sits on the nominating committee, has a higher level of share ownership, or the board has more executive directors). This result is in sharp contrast to the US where compensation is influenced by CEO power. Overall our findings are more consistent with the predictions of the incentive alignment theory rather than the managerial power theory.